The massacre of mankind : sequel to the war of the worlds authorized by H.G. Wells - Baxter, Stephen (Crown, 2017)
"A sequel to the H.G. Wells classic THE WAR OF THE WORLDS, brilliantly realized by award-winning SF author and Wells expert Stephen Baxter. It has been 14 years since the Martians invaded England. The world has moved on, always watching the skies but content that we know how to defeat the Martian menace. Machinery looted from the abandoned capsules and war-machines has led to technological leaps forward. The Martians are vulnerable to earth germs. The Army is prepared. So when the signs of launches on Mars are seen, there seems little reason to worry. Unless you listen to one man, Walter Jenkins, the narrator of Wells' book. He is sure that the Martians have learned, adapted, understood their defeat. He is right. Thrust into the chaos of a new invasion, a journalist - sister-in-law to Walter Jenkins - must survive, escape and report on the war. The Massacre of Mankind has begun"--